Highly Stable and Scalable Lithium Metal Anodes Enabled by a Lithiophilic SnO2@Graphite Fiber Framework Design. Issue 8 (23rd June 2022) - Qian, Xiaojuan; Miao, Di; Lin, Xiaoping; Chen, Maohua; Xie, Yuansen; Qu, Jie; Tu, Xingchao; Lai, Chao
Abstract: The uncontrollable growth of dendrites, infinite volume changes, low Coulombic efficiencies, and poor charging/discharging rates in lithium metal anodes have seriously hampered the further development of lithium metal batteries. Trapping lithium (Li) into rationally designed three‐dimensional (3D) structured Li metal anodes in order to construct a 3D‐Li framework is an effective approach to suppress the growth of Li dendrites. However, material inconsistencies and high costs still seriously limit practical applications. In this study, we describe the use of commercial low‐cost graphite fiber (GF) as a suitable conformal scaffold for preparing a lithiophilic SnO2 @GF material using facile infiltration method. The lithiophilic 3D porous conductive framework allows homogeneous Li deposition on the surface of a structured electrode and accommodates the volume change during Li plating/stripping, leading to a significant boost in both the charging/discharging rates and cycling stability. This study highlights the significance of interface‐related science and engineering in designing high‐performance Li metal anodes, but also highlights the need for greater dedication to the construction of highly stable lithium anodes and high‐energy density Li metal batteries in a low‐cost manner. Abstract : Lithiophilic fiber : Lithiophilic 3D porous and conductive SnO2 @graphite fiber framework was prepared via a facile infiltration method, which can regulate homogeneous Li deposition and accommodate the volume change during repeated plating/stripping, thus leading to significant boost in both cycling stability and charging/discharging rates.